Function of obturator prosthesis after maxillectomy and prosthetic obturator rehabilitation - Chen,Cheng (2016)
ABSTRACT INTRODUCTION: Maxillary defects are usually rehabilitated by a prosthetic obturator. OBJECTIVE: This study aimed to evaluate the functioning of obturators prosthesis in patients with unilateral defects after maxillectomy. METHODS: Of 49 patients, 28 underwent to maxillectomy as a result of tumor ablative surgery, and acquired unilateral maxillary defects. Evaluation of the function was performed by applying the Obturator Functional Scale (OFS). RESULTS: From a total of 49 patients, 28 were treated as follows: 9 with a conventional retained obturator prosthesis (COP), 11 (39%) with an enhanced retentive obturator prosthesis with stud attachment (POP) and 8 (28%) with an enhanced retentive obturator prosthesis with magnetic attachment (POM). The mean OFS score was 80. Scores on functions of speech, swallowing and chewing reached statistical significances (p < 0.05) among these three subgroups. Comparing COP and MOP groups, the scores of OFS in the domains of "Speech-ability to speak in public" and "Swallowing-leakage with liquids" were significantly higher in AOP group. Comparing COP group, the scores of OFS in "Swallowing-leakage with solid" and "Chewing/eating" domains were increased significantly (p < 0.05) both in MOP and AOP groups. CONCLUSION: Obturator prosthesis improves oral function of patients after maxillary defects; the retention of the obturator prosthesis enhanced by the addition of attachments showed more benefits in oral function.